The changes of trace elements, malondialdehyde levels and superoxide dismutase activities in pregnancy with or without preeclampsia - Ilhan, N; Ilhan, N; Simsek, M (Pergamon-Elsevier Science Ltd, 2002)
Objectives: Increased free radical activity and lipid peroxidation may be implicated in the pathogenesis of preeclampsia, This study was initiated to assess antioxidant enzyme and trace metals's status in preeclampsia. Design and methods: The comparision was made between the pregnant women with or without preeclampsia and healthy controls' in this study. Samples were obtained from 24 normal nonpregnant (controls), 30 normal pregnant and 21 preeclamptic women in the third:trimester. Lipid peroxidation end product, malondialdehyde (MDA), free radical scavenging enzyme activity, superoxide dismutase (SOD) and serum zinc (Zn), copper (Cu) levels were measured in either plasma/serum or erythrocytes of patients. Data were analyzed statistically using Student's t-test. Results: In the preeclamptic group malondialdehyde, Cu levels were significantly increased, while Zn and SOD levels were significantly decreased compared to normal control group and healthy pregnant women. Conclusions: Our findings give support that radical scavenging SOD is consumed by the increased lipid peroxidation in preeclampsia. This data may indicate an involvement of free radicals in the pathophysiology of preeclampsia. This study suggests a relationship between increased MDA, Cu levels and decreased SOD, Zn levels in pregnancy and preeclampsia. (C) 2002 The Canadian Society of Clinical Chemists. All rights reserved.
Keywords: lipid peroxidation; antioxidant enzyme; trace metals; preclampsia